Evaluation of Preptin and other Biomarkers in Coronary Artery Disease Patients with and without Diabetes Mellitus - Saja T. Yassen; Layla O. Farhan (مجلة كلية الطب)
Background: Preptin is an endocrine peptide with 34 amino acids. Conjugated with insulin, it is produced by β-cells from the pro-insulin-like growth factor 2 E-peptide. However, in addition to insulin, pancreatic hormone (Preptin) is released in response to elevated blood glucose levels. Preprint’s primary metabolic effect is to raise insulin synthesis, which is achieved through both an amplifying mechanism and a triggering route that is dependent on calcium signalling.